2014
DOI: 10.31018/jans.v6i2.482
|View full text |Cite
|
Sign up to set email alerts
|

Yield, water use and water use efficiency of pigeonpea [Cajanus cajan (L.) Millsp.] under drip fertigation system

Abstract: Abstract:Field experiments were carried out during two seasons (August-February) of 2011-12 and 2012-13 at Millet Breeding Station, Tamil Nadu Agricultural University, Coimbatore, to study the effect of drip fertigation on productivity, water use and water use efficiency of pigeonpea (Cajanus cajan) cv. LRG 41. The treatments included three irrigation regimes (50 %, 75 %, 100 % computed water requirement of crop) and surface irrigation along with three fertilizer levels with water soluble fertilizer (WSF) and … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
3
0

Year Published

2017
2017
2024
2024

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 8 publications
(4 citation statements)
references
References 1 publication
0
3
0
Order By: Relevance
“…Markedly higher W UE was recorded with higher level of fertigation than lower level, because of adequate and timely availability of water and nutrients and their positive interaction might have simulated the early growth and increased the yield to record higher WUE under drip fertigation with higher levels compared to soil application of fertilizers. Praharaj et al (2014), Vimalendran and Latha (2014), Praharaj et al (2016) also reported the similar finding of increasing water use efficiency with increasing level of fertigation. Maximum nutrient use efficiency was observed in all the treatments where fertilizer was applied as fertigation in five splits as compared to soil application of fertilizer in furrow and drip irrigation.The nutrient use efficiency was considerably increased in drip fertigation compared to soil application of N, P and K fertilizers.…”
Section: Response Of Split Application Of Nutrients Through Fertigatimentioning
confidence: 66%
“…Markedly higher W UE was recorded with higher level of fertigation than lower level, because of adequate and timely availability of water and nutrients and their positive interaction might have simulated the early growth and increased the yield to record higher WUE under drip fertigation with higher levels compared to soil application of fertilizers. Praharaj et al (2014), Vimalendran and Latha (2014), Praharaj et al (2016) also reported the similar finding of increasing water use efficiency with increasing level of fertigation. Maximum nutrient use efficiency was observed in all the treatments where fertilizer was applied as fertigation in five splits as compared to soil application of fertilizer in furrow and drip irrigation.The nutrient use efficiency was considerably increased in drip fertigation compared to soil application of N, P and K fertilizers.…”
Section: Response Of Split Application Of Nutrients Through Fertigatimentioning
confidence: 66%
“…Latha et al (2012) reported that direct sown pigeonpea (CO 6) at single row per lateral with 10 split application of N and K through drip fertigation + 100 per cent WRc recorded the highest grain yield (1486 kg ha -1 ), net income and B:C ratio over different spacing in transplanted pigeonpea in the Western Zone of Tamil Nadu. Vimalendran and Latha (2014) revealed that drip irrigation at 100 % WRc with fertigation at 125 % RDF through WSF registered significantly highest grain yield of 2812 and 2586 kg ha -1 during 2011-12 and 2012-13, respectively.…”
Section: Effect Of Drip Fertigation On Growth and Yield Attributesmentioning
confidence: 97%
“…Irrigation method: The choice of irrigation method depends on the soil type, water availability and crop requirements. Sprinkler and drip irrigation systems are popular for pulse crops [17,18]. 6.…”
Section: Irrigationmentioning
confidence: 99%